Integrated Programmes for Master's Degree and PhD Students - Boris I. Bednyi; Oleg A. Kuzenkov (National Research Mordova State University, 2017)
Introduction: the aim of this study is to develop a new model for training highly qualified academic and research staff based on the integration of academic master's degree and PhD programmes. The new model of research-focused education is based on the continuity of PhD programmes with academic master's programmes. It enables the implementation of consistent development of research and teaching competencies within the framework of a single educational path aimed at defending the PhD thesis. Such integrated programmes are intended to ensure (both organisationally and in terms of content) that students are adequately prepared for a professional career in the academic field. Materials and Methods: the methodological basis for creating this model is provided by the competencybased approach. The methods for developing integrated educational programmes "Academic master - PhD studies" include the coordination of the systems of competencies for the second and third levels of higher education, as well as the application of the modular approach in curriculum design, thus helping to optimise the content of training of professional researchers and teachin g staff for higher education institutions. Results: a new approach to the organisation of targeted training of research and teaching staff has been developed. This approach provides for the unity and continuity of research and educational components of training at the second and third levels of higher education and ensures the creation of optimal individual educational paths leading to the defense of the PhD thesis. A model of integrated programmes "Academic masters - PhD studies" has been developed, which is explained on the example of training experts in the field of mathematical modeling. Discussion and Conclusions: the model of education at the second and third levels of higher education proposed in this paper enables an optimal organisation of academic programmes aimed at training research and teaching staff for universities. The results of the work may be of interest to researchers of higher education, as well as to research, teaching and administrative staff members of higher education institutions dealing with the issues of PhD training and certification.